Principle of Original Authority In Territorial Decentralization - Sultoni Fikri; Rizky Bangun Wibisono (CV. Era Digital Nusantara, 2023)
Abstract: Indonesia is a unitary state, where within the framework of the unitary state, power is divided between the central government and regional governments. The regional government is divided into three levels, namely provincial, district, and city regional government. The division of powers to local governments is interpreted as the principle of autonomy. In the NA RUU-Pemda as well as the General Elucidation of the UU-Pemda, it is implied and stated that the autonomy that exists in an autonomous region is a gift. Meanwhile, from the point of view of its establishment, regional autonomy is original, not granted, and is a regional right based on its principle. In principle, the regional right to regulate and manage it is an original right and is not a gift from the central government. From this principle, provisions were born which stated that provincial, regency, and city regional governments regulate and manage their own government affairs according to the principles of autonomy and co-administration. Purpose: The purpose of this study is to explain that regional autonomy is not a gift from the central government but the original authority possessed by the regional government. Design/Methodology/Approach: This research is legal research. The approach method used in this study is to use a statutory approach, historical approach, and conceptual approach. Findings: In principle, the right of the region to regulate and manage it is an original right and is not a gift from the central government. From this principle, the provisions of Article 18 paragraph (2) were born which states that provincial, regency, and city regional governments regulate and manage their own government affairs according to the principles of autonomy and co-administration. Originality/Value: This research tries to explain that regional autonomy in Indonesia is a regional original right, not the result of a gift from the central government. because in several studies that raise regional autonomy, it is always explained that the autonomy obtained by the regional government is the result of a gift from the central government. The difference in point of view is what makes this research a novelty.